Experiences with Coding using ICD-11: “The Codes Paint a Clearer Picture” - Eastwood, Catherine; Southern, Danielle; Boxill, Alicia; Maciszewski, Malgorzata; Quan, Hude; Cullen, Denise; Penchoff, Margaret; Ghali, William (International Journal of Population Data Science, 2018)
Introduction A high performing health data classification system requires clear, comprehensive code descriptions and user-friendly coding tools for effective coding. Coding specialists have essential specialized knowledge to contribute to the development and functionality of the 11th version of International Classification of Diseases (ICD-11) that will be released in June of 2018. Objectives and Approach The objective was to evaluate coding specialists’ experience of coding using ICD-11 for complete inpatient hospital charts. Mixed methods were employed for a survey and interviews. As part of a large field trial, 6 certified coding specialists underwent training to use the ICD-11 Beta Draft browser and ICD-11 Coding Tool. The coding team completed multiple coding exercises and coded over 60 charts each prior to evaluation of their experience. An electronic survey was used to evaluate ICD-11 knowledge, comprehension, and application of the coding training. Interviews explored the coders’ experience of learning and using the ICD-11 classification system. Results The coding team (3 to 10 years of experience) received 14 hours classroom training and 5-10 hours per week of coding practice over 3 months. After training, perceived confidence in coding with ICD-11 was satisfactory; moderate (n=4), high (n=1), and low (n=1). Coding short scenarios was the most useful resource (n=6) and lack of guidelines was the most frustrating. Learning ICD-11 was deemed moderately (n=2) to somewhat (n=3) difficult but each coder described satisfaction in learning the new system. From the interviews, coders expressed liking the ability to more fully describe health conditions and hospital harms with code clusters. “The codes paint a clearer picture of what happened than with ICD-10”. With practice they achieved speed with the coding tools. Conclusion/Implications Coding specialists learned and proficiently used the Beta Version of ICD-11 coding system with moderate perceived confidence. New ICD-11 codes and clustering functions allowed for more complete description of health scenarios and enhanced coder satisfaction.